Paternal age and the risk of cerebral palsy - Sternal, Marta; Kwiatkowska, Barbara; Borysławski, Krzysztof; Tomaszewska, Agnieszka (Anthropological Review, 2020)
In the literature there are no unequivocal assessments of the effect of paternal age on the risk of cerebral palsy (CP). The objective of the studies was the analysis of the influence of paternal age on this risk, considering all the important risk factors and division into singleton and twin, as well as term- and preterm-born infants. The inquiry included a group of 278 children with cerebral palsy from selected education-therapeutic institutions in Poland. The control group consisted of the data from medical records of 435 neonates born in God’s Mercy Hospital in Limanowa, Poland. The data were based on a questionnaire designed to obtain information which would make it possible to ascertain the probable etiological factors. Constructed models of logistic regression were used in statistical analysis. The results were presented as the odds ratio (OR) with 95% confidence interval (CI). Though the estimation with a complex model of logistic regression showed no significant effect of paternal age on the occurrence of cerebral palsy, it confirmed it as a stronger predictor compared to maternal age. Disregarding paternal of age while considering maternal age and other risk factors may lead to a bias in the estimations of the risk cerebral palsy.